Sampling and monitoring for the mine life cycle - McLemore, Virginia T.; Smith, Kathleen S. (Geologist); Russell, Carol C. (Management Technologies for Metal Mining Influenced Water, Volume 6., 2014)
Sampling and Monitoring for the Mine Life Cycle provides an overview of sampling for environmental purposes and monitoring of environmentally relevant variables at mining sites. It focuses on environmental sampling and monitoring of surface water, and also considers groundwater, process water streams, rock, soil, and other media including air and biological organisms. The handbook includes an appendix of technical summaries written by subject-matter experts that describe field measurements, collection methods, and analytical techniques and procedures relevant to environmental sampling and moni.